Enhanced bamboo interfacial bonding performance on the basis of toughening phenol formaldehyde resin by flour. Issue 1 (19th October 2022) - Jiang, Haochong; Du, Yuting; Wang, Jinhui; Cao, Yizhong; Jin, Chunde; Yan, Yutao
Abstract: Phenol formaldehyde (PF) resin adhesive is the most commonly used adhesive in bamboo gluing due to its excellent bonding strength and durability. However, its high brittleness after curing could cause stress concentration at the bonding interface between PF resin and bamboo, which seriously affect the bonding performance. In this study, different quantity of flour was incorporated into PF resin adhesive and homogeneous processed, the toughening effect and mechanism of the flour on PF resin together with the influence on the bonding strength were fully investigated. Differential scanning calorimeter analysis indicated that flour could make the curing reaction of PF resin much milder. Fracture morphology characterization of PF resin by scanning electron microscopy showed that the flour had good dispersibility and compatibility in PF resin adhesive, which could directly contribute to the mechanical properties of PF resin specimens by forming a ductile fracture. When 10 wt% flour was incorporated, the flexural and impact strength increased by 83.42% and 92.01% compared with the pure PF resin, respectively. The decreased quantity and size of the cracks in cured PF resins on bamboo surface after the incorporation of flour observed by Ultra‐depth‐of‐field microscope and quasi‐static nanoindentation of bonding interface proved that flour could effectively toughen the PF resin and reduce the formation of defects and cracks inside the resin, thus improve the bonding strength. Correspondingly, the bonding strength of the PF resin adhesive glued bamboo strips increased by 14.5% when 10 wt% flour was added into the PF resin. Abstract : Different quantity of flour was incorporated into PF resin adhesive and homogeneous processed, the toughening effect and mechanism of the flour on PF resin together with the influence on the bonding strength were fully investigated.